Pendampingan Penanaman Nilai Budaya dan Seni Jawa Pada Anak Transmigran di Sanggar Belajar Ndeso Berdaya Desa Margotani II - Saputra, Ardi; Septiani, Yiyin; Andriani, Dian Sri; Helmi, Henny; Septiyanda, Dwi; Pitayati, Puspa Ayu (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
The community service program, Mentoring the Instillation of Javanese Cultural and Art Values in Transmigrant Children at the Sanggar Berdaya Desa Margotani II, aims to overcome the declining understanding of Javanese culture and art among transmigrant children. This activity involved 26 transmigrant children who were Sanggar Berdaya Desa Margotani II students. This activity was carried out using the lecture, question and answer, and direct practice methods with participants. The stages of this activity include the presentation of material using the lecture method on the history of the transmigration program, the variety of Javanese culture and art, traditional games, and tourism. The next stage is a question and answer session with participants to strengthen their knowledge and understanding. The community service team also handed over technological innovation aids to the community through the Kawruh Basa Jawa book and a mini Saron musical instrument used during the practice. The next activity was the practice of reading and writing Javanese script, the practice of traditional Javanese dance, and traditional Javanese games. The results of this program showed an increase in participants' knowledge and enthusiasm for Javanese culture and art. It can be concluded that this program contributes to the sustainability of Javanese cultural and arts learning for future generations, while also demonstrating the potential of community-based learning centres in building cultural resilience and strengthening social cohesion in transmigrant environments. to increase cultural appreciation, preserving Javanese cultural heritage, and enhance social harmony in transmigrant communities.ABSTRAKProgram pengabdian kepada masyarakat bertajuk Pendampingan Penanaman Nilai Budaya dan Seni Jawa pada Anak Transmigran di Sanggar Belajar Ndeso Berdaya, Desa Margotani II bertujuan untuk mengatasi menurunnya pemahaman budaya dan seni Jawa pada anak-anak transmigran. Kegiatan ini melibatkan 26 anak transmigran yang merupakan warga belajar Sanggar Berdaya Desa Margotani II. Kegiatan ini dilakukan dengan metode ceramah, tanya jawab, dan praktik langsung dengan peserta. Tahapan kegiatan ini meliputi pemaparan materi dengan metode ceramah tentang sejarah program transmigrasi, ragam budaya dan kesenian Jawa, permainan tradisional serta kepariwisataan. Tahapan selanjutnya adalah tanya jawab kepada peserta untuk memperkuat pengetahuan dan pemahamannya. Tim pengabdian juga menyerahkan alat bantu inovasi teknologi kepada masyarakat berupa buku Kawruh Basa Jawa dan alat musik saron mini yang digunakan pada saat praktik. Kegiatan selanjutnya adalah praktik membaca dan menulis aksara Jawa, praktik seni tari tradisional Jawa, dan permainan tradisional Jawa. Hasil program ini menunjukkan bertambahnya pengetahuan dan antusiasme peserta terhadap budaya dan seni Jawa. Dapat disimpulkan, program ini memberikan kontribusi terhadap keberlanjutan pembelajaran budaya dan seni Jawa bagi generasi mendatang, sekaligus menunjukkan potensi sanggar belajar berbasis komunitas dalam membangun ketahanan budaya dan memperkuat kohesi sosial di lingkungan transmigran. untuk meningkatkan apresiasi budaya, melestarikan warisan budaya Jawa, serta memperkuat harmoni sosial di komunitas transmigran.